Evaluate the effect of surface treatments on shear bond strength between lithium disilicate ceramic and dentin. - Chakmakchi, Makdad (Journal of Baghdad College of Dentistry, 2017)
Purpose: To evaluate the effect of different surface treatments on shear bond strength between dentin and IPS e.max lithium disilicate glass-ceramic.Materials and Methods: Eighteen extracted third molars were embeded in epoxy resin. The tooth was sectioned vertically in mesiodistal direction using a low speed hard tissue microtome. The buccal and lingual surfaces of each section were ground flat using 600 grit Silicone carbide paper. Eighteen ceramic discs consisted of lithium disilicate glass-ceramic were prepared with a diameter of 4.7mm and height of 2.2mm. The discs were divided in two groups (n=10): (1) IPS e.max treated with hydrofluoric acid and Monobond Plus (MBP) and (2) IPS e.max treated with Monobond Etch &Prime (MBEP). The tooth was cemented with Multilink Automix and stored for 24hours at room temperature before thermocycling and subsequently loaded to failure in Universal Testing Machine. Failure mode were recorded for each specimen. Result: Bond strength analysis and t-test analysis MBEP demonstrated the higher shear bond strength (SBS). MBP and MBEP showed no statistically significant difference were found between them. One-way ANOVA and t-test was used to determine differences in bond strength within and between the groups. Cohesive failure in resin cement was predominant with higher results while adhesive and mixed with lower and equal.Conclusion: Surface treatment with Monobond Etch and Prime has a favorable effect on SBS between dentin and lithium disilicate glass-ceramic with resin cement compared with Monobond Plus.